The synegistic impact of organisational culture and digital transformation in enhancing organizational performance and efficiency in public sector institutions - Myres, Hugh (University of Pretoria, 2026)
Mini Dissertation (MPhil (Corporate Strategy))--University of Pretoria, 2025.